Underweight in young Japanese women over time: a longitudinal retrospective study of the change in body mass index from ages 6 to 20 years - Yuka Nagashima; Mikako Inokuchi; Yasunori Sato; Tomonobu Hasegawa (Annals of Human Biology)
Background The high prevalence of underweight in young women has become a serious health problem in Japan. When and how young women reach a low body mass index (BMI) has not been clarified.Aim To clarify the characteristics of BMI standard deviation scores (BMI SDS) trajectory of young Japanese women with underweight.Subjects and methods A total of 601 Japanese female university students aged 20 years were classified into underweight and healthy weight groups. Their school health check-up data were available from the ages of 6 to 20 years. We evaluated the estimated mean values of BMI SDS at each age and differences in BMI SDS (ΔBMI SDS) from 6 years to each age using a mixed-effects model and compared between the two groups at each age.Results In the underweight group, the BMI SDS at every age (−1.67 to −0.91) and the ΔBMI SDS after 16 years of age (−0.76 to −0.38) were significantly lower than those in the healthy weight group (−0.41 to −0.13, −0.07 to 0.04), respectively.Conclusion Young Japanese women with underweight have at least two characteristics of BMI SDS trajectory: being constitutionally underweight and shifting their weight status from baseline towards underweight in their late teens.